Genetic polymorphisms of TRAPPC9 and CD4 genes and their association with milk production and mastitis resistance phenotypic traits in Chinese Holstein - Khan, Muhammad Zahoor; Dari, Gerile; Khan, Adnan; Yu, Ying (Frontiers in Veterinary Science, 2022)
The present study was designed to evaluate the association of polymorphisms in bovine TRAPPC9 and CD4 genes with milk production and mastitis resistance phenotypic traits in a different cattle population. Three single nucleotide polymorphisms (SNPs) (SNP1 Position: Chr14:2484891, SNP2 (rs110017379), SNP3 Position: Chr14:2525852) in bovine TRAPPC9 and one SNP (Position: Chr5:104010752) in CD4 were screened through Chinese Cow’s SNPs Chip-I (CCSC-I) and genotyped in a population of 312 Chinese Holsteins (156: Mastitis, 156: Healthy). The results were analyzed using the general linear model in SAS 9.4. Our analysis revealed that milk protein percentage, somatic cell count (SCC), somatic cell score (SCS), serum cytokines interleukin 6 (IL-6) and interferon-gamma (IFN-γ) were significantly (P<0.05) associated with at least one or more identified SNPs of TRAPPC9 and CD4 genes. Furthermore, the expression status of SNPs in CD4 and TRAPPC9 genes were verified through RT-qPCR. The expression analysis showed that genotypes GG in SNP3 of TRAPPC9 and TT genotype in SNP4 of CD4 showed higher expression level compared to other genotypes. The GG genotype in SNP2 and TT genotype in SNP3 of TRAPPC9 were associated with higher bovine milk SCC and lower IL6. Altogether, our findings suggested that the SNPs of TRAPPC9 and CD4 genes could be useful genetic markers in selection for milk protein improvement and mastitis resistance phenotypic traits in dairy cattle. The CCSC-I used in current study is proposed to be validate in different and large population of dairy cattle not only in China but also in other countries. Moreover, our analyses recommended that besides SCC and SCS, the association of genetic markers could also be establish with the serum cytokines (IL-6, IFN-γ) while selecting genetically mastitis resistance dairy cattle.